UPAYA PENAGGULANGAN GELANDANGAN DAN PENGEMIS DI KECAMATAN MARTAPURA KOTA KABUPATEN BANJAR (Perda Kabupaten Banjar Nomor 2 Tahun 2014 Tentang Penanggulangan Gelandangan dan Pengemis) - tamliha harun (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2018)
This research was conducted with the aim to find out more about the efforts made by the Banjar Regency Government in tackling the problem of homelessness and beggars in Martapura Kota District, Banjar Regency. It is expected that the results of this study can provide input for the Banjar Regency Government in an effort to maximize the sprawl response in the region. This research is a descriptive study, with data collection techniques: interviews, observation, and documentation, then the results are analyzed qualitatively. The results of this study indicate that: a. Sprawl in Banjar District (especially in Martapura Kota District) has been carried out through preventive efforts, repressive measures, and rehabilitation (rehabilitative) efforts based on Regional Regulation Number 2 of 2014 concerning Countermeasures for Homelessness and Beggars; b. These sprawl countermeasures are still not optimal, if referred to the regional regulation which covers them, especially rehabilitation efforts have not been carried out properly; c. The efforts of the sprawl control have not yet been maximized due to several obstacles, including the lack of apparatus (Social Service and Satpol PP), the lack of available budget allocations, and the unavailability of flat construction facilities and infrastructure as needed; d. Criminal sanctions and non-criminal sanctions in accordance with the Regional Regulation, cannot yet be applied firmly and consistently to sprites who have committed violations, as a result sanctions imposed on sprawl do not cause a deterrent effect.